Economic Sensitivity Analysis of Waste Heat Recovery System in PME Biodiesel-Fueled Industrial Diesel Generators - Erwin Budi Sulistyo (Publica Scientific Solution, 2026)
This study analyzes the economic sensitivity of an exhaust gas waste heat utilization system in a PME biodiesel-fueled industrial diesel generator to replace electrical heating energy in the biodiesel preheater system. Investment feasibility was evaluated using Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PBP) under variations in electricity tariffs, annual operating hours, capital expenditure (CAPEX), and discount rates. The baseline analysis indicates strong financial feasibility, yielding an NPV of IDR 2,229,466,230, an IRR of 93.7%, and a payback period of 1.07 years. Sensitivity analysis shows that the electricity tariff is the most dominant parameter affecting investment viability. Based on a linear interpolation approach, the investment reaches its break-even point at an electricity tariff of approximately IDR 435/kWh. Overall, the system demonstrates robust economic resilience and strong potential for energy conservation and industrial decarbonization under the framework of Economic Sensitivity Analysis of Waste Heat Recovery System in PME Biodiesel-Fueled Industrial Diesel Generators.